2021
DOI: 10.3233/xst-200780
|View full text |Cite
|
Sign up to set email alerts
|

Optically transparent glass modified with metal oxides for X-rays and gamma rays shielding material

Abstract: BACKGROUND: Metal oxide glass composites have attracted huge interest as promising shielding materials to replace toxic, heavy, and costly conventional shielding materials. OBJECTIVE: In this work, we evaluate shielding effectiveness of four novel tellurite-based glasses samples doped with oxide metals (namely, A, B, C, and D, which are 75TeO2- 10P2O5- 10ZnO- 5PbF2- 0.24Er2O3 ; 70TeO2- 10P2O5- 10ZnO- 5PbF2 -5MgO- 0.24Er2O3; 70TeO2- 10P2O5- 10ZnO- 5PbF2- 5BaO- 0.24Er2O3 ; and 70TeO2- 10P2O5-10ZnO- 5PbF2- 5SrO; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Cement and concrete, which are bulky and prone to cracking, are mainly used for fixed protection, such as in buildings [21,22], while lead shielding materials have poor mechanical strength, are toxic, scatter more low-energy X-rays, and are more costly [23,24]. Although iron-based metal materials have high specific gravity and high mechanical strength, they are costly and have singular performance [25]. It is undoubtedly wise to choose a cheap alternative and prepare it as a composite material.…”
Section: Introductionmentioning
confidence: 99%
“…Cement and concrete, which are bulky and prone to cracking, are mainly used for fixed protection, such as in buildings [21,22], while lead shielding materials have poor mechanical strength, are toxic, scatter more low-energy X-rays, and are more costly [23,24]. Although iron-based metal materials have high specific gravity and high mechanical strength, they are costly and have singular performance [25]. It is undoubtedly wise to choose a cheap alternative and prepare it as a composite material.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the dramatic increase in the use of radiation in medical and industrial applications, radiation shielding issues have become an important topic among researchers [ 1 , 2 , 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Much research has been conducted to study the effectiveness of glass as a radiation shield [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. All results concluded that glass could offer excellent shielding against radiation for different applications, such as nuclear power plants, agricultural machinery, industrial processes, and medical applications [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted to develop alternative materials that replace lead such as tellurite base glasses, phosphate-based materials, metal alloy, polymers [16][17][18][19][20][21][22][23][24][25]. These studies showed a good shielding performance in terms of high shielding efficiency without loss of transparency, good physical properties, thermal stability, and good optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The shielding effectiveness has been studied in terms of the physical properties, radiation shielding parameters, LAC, MAC, HVL, MFP, Z eff, and N eff . Hussein, et al [16] have studied the shielding effectiveness of four novel tellurite-based glasses samples doped with oxide metals (75TeO…”
Section: Introductionmentioning
confidence: 99%